Promising COVID-19 therapies on examples of some antiviral, immunomodulatory and natural substances use - review - Bielewicz, Krzysztof; Ryba, Karolina; Karaś, Anna; Kawałko, Kinga; Pondel, Kamil (Journal of Education, Health and Sport, 2022)
COVID-19 is one of the biggest challenges to medicine ever. Because of its dissemination in population effective drug to cure it was needed. There were some trials on antiviral drugs like lopiravir/ritonavir, remdesivir, darunavir/cobicistat, favipiravir, molnupiravir, discovered originally in order to treat other diseases. Only remdesivir and molnupiravir seem to be beneficial for patients with COVID-19, both of them are approved in therapy in a large number of countries allover the world. [2] Another very important group of drugs used in trials against COVID-19 was immunomodulatory drugs. Some of them, like chloroquine/hydrochloroquine was very promising, but finally there were no evidences of its benefits found. [2] Corticosteroids used in moderate and severe COVID-19 caused general improvement of clinical status and decreased mortality. Interesting and quite promising may be use of interferons but for now lack of evidences does not allow to make clear statement about its benefits. There are some argumentations for natural methods of COVID-19 treatment. Dietary recommendations, vitamin and microelements supplementation may be helpful in the therapy and in addition may not have any adverse effects. Also, herbal mixtures, developed centuries ago in China found usage during COVID-19 pandemic. After analysis of thousands of cases Traditional Chinese Medicine can be considered as one of the most successful attempt in combating COVID-19. [6]